Clinical Duration as a Predictor for Bowel Resection in Intussusception - Juliansyah, Amir; Sastiono, Sastiono (The New Ropanasuri Journal of Surgery, 2017)
Introduction. Delayed hospital presentation is a characteristic we found in management of intussusception in our institution. However, with this delayed, surgical intervention is the only option in treatment. Thus, duration of onset is an answered problem. We run a study aimed to find out whether duration is a predictor of bowel resection in management of intussusception. Method.We run retrospective study on idiopathic intussusception managed in period of January 2008 to December 2015 in Cipto Mangunkusumo Hospital, Jakarta. Those other than idiopathic and insufficient data were excluded. Period of onset, signs and symptoms, ultrasound and surgical treatment as well as intraoperative findings were set as the variables and subjected to statistical analysis using χ2 or Fisher’s exact test and t–test; significance is met if p value of <0.05. Analysis to find out cut–off point using receiver operating characteristic curve were carried out. Results. There were seventy–three subjects diagnosed as intussusception enrolled in the study. Median age was 7 months (3-48 month). Median period of onset to definitive treatment was 81 hours (15-256 hours). Bloody stools found in 90.4% instead of classic triad (28.7%). All subjects underwent surgical procedure, and out of 73 subjects, 61.6% underwent resection. We found clinical duration was associated to bowel resection (p 0.004) and area under curve 73.7% (p 0.001). The cut–off point as prediction of bowel resection was 78.5 hours with sensitivity of 67.9% and specificity of 71.1%. Conclusion. Surgical intervention is recommended for management of intussusception in those with clinical duration of more than 78.5 hours, instead of non–surgical reduction.